Peran Pemerintah dalam Implementasi Program Pemberdayaan UMKM di Kota Makassar: Studi pada Akses Modal dan Pelatihan - Nasir, Nasir (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to analyze the role of the government in the implementation of MSME empowerment programs in Makassar City, with a focus on access to capital and training. MSMEs have an important role in the regional economy, but they still face various challenges, especially in obtaining financing and increasing business capacity. This study uses a qualitative approach with a case study method. Data was collected through interviews with MSME actors, government representatives, and financial institutions, and was strengthened by observation and documentation studies. The results of the study show that the Makassar City government has provided various capital access programs, such as People's Business Credit (KUR) and revolving capital assistance, which help MSMEs in business development. However, there are still obstacles in the complex administrative process, requirements that are difficult to meet, and lack of socialization. In terms of training, the program has improved the skills of MSME actors, especially in digital marketing and product innovation. Nevertheless, the sustainability of the program and post-training mentoring are still a major challenge. The novelty of this research lies in an in-depth analysis of the synergy between the government, financial institutions, and the business community in empowering MSMEs. The implication is that the government needs to simplify capital access procedures, increase the effectiveness of training through a technology-based approach, and strengthen mentoring programs for MSMEs. This research contributes to the development of more inclusive and sustainable policies to support the growth of MSMEs in Makassar City.